New insights in the development of syn‐depositional fractures in rimmed flat‐topped carbonate platforms, Neogene carbonate complexes, Sorbas Basin, SE Spain. (3rd May 2017) - Nooitgedacht, Casimir W.; Kleipool, Lucas M.; Andeweg, Bernd; Reolid, Jesús; Betzler, Christian; Lindhorst, Sebastian; Reijmer, John J. G.
Abstract: The formation of syn‐depositional fractures in carbonate platforms is considered an important feature in the understanding of platform evolution. This study investigates the mechanisms of fracture formation in rimmed flat‐topped carbonate platforms in the very well‐exposed Cariatiz Miocene Fringing Reef Unit, SE Spain. Fracture data were obtained using a combination of LIDAR and field mapping techniques, which proved useful in understanding general fracture trends. The morphological expression of fracture sets, preferred fracture localization, crosscutting relationships and fracture fill are characteristics that provide constraints on the timing of fracture formation and opening. Three dominant fracture populations were identified, amongst which a margin parallel and a margin perpendicular fracture set. Margin parallel fractures localize around the platform margin and form vertically extensive dikes that crosscut facies boundaries. The sedimentary fill of such fractures suggests syn‐depositional fracture formation under marine conditions. Together, fracture characteristics suggest a gravitational driver for the formation of tensile stress and the development of margin parallel fractures along the platform edge. Margin perpendicular structures form sub‐vertical dikes and fracture corridors. Margin perpendicular fractures localize on the platform slope and show two types of fracture fill, indicating marine and continental origins. Based on variations of fracture morphology along the carbonate platform, fracture localization, petrographic analysis of sedimentary fill and stable isotope analysis on sparite cements, we suggest a gravitational control on the formation of these fractures. Two mechanisms for the formation of subvertical margin perpendicular fractures are proposed: (1) principal stress rotation as a result of downslope loading. (2) Differential compaction over buried gulley systems on antecedent clinoform slopes. We suggest that the formation of sub‐vertical margin perpendicular fractures might be a systematic feature in slopes of flat‐topped carbonate platforms.